EFFECTS OF SEASON, SEX AND TIME OF DAY ON OSTRICH BREEDER (Struthio camelus) BEHAVIOR - Bilgehan YILMAZ DIKMEN (Journal of Animal and Plant Sciences, 2024)
Ambient temperature has a crucial effect on livestock production performance, behaviors and welfare. In ostrich, previous research primarily focused on survival and reproductive performance during the climatic shifts. This study was carried out to investigate the effect of seasonal variation on behavioral differences of male and female ostrich (Struthio camelus) breeders, reared in farm environment. The individual behaviors related to digestion, locomotor activities, resting, comfort and thermoregulation, reproduction, and aggressive behaviors were recorded. The higher sitting and sleeping behavior were observed in summer season (P<0.01 and P<0.001, respectively). The thermoregulation behaviors were observed only in summer season (P<0.0001). The higher foraging, alertness and spot pecking behaviors were observed in females (P<0.01, P<0.05, and P<0.05, respectively). The boom behavior was only observed in males (P<0.05). The higher walking behavior was observed in the afternoon and morning (P<0.05). The higher sleeping, dust bathing, grooming and thermoregulation behaviors were observed at noon (P<0.001, P<0.001, P<0.0001 and P<0.0001, respectively). There was a significant interaction between season and sex for displace behavior, a sign of aggressive behavior (P=0.006). There was a significant interaction between season and time of day for drinking and defecation related to digestive behaviors (P<0.05 and P<0.05, respectively); sleeping described as a resting behavior (P=0.0001); dust bathing and grooming which is related to comfort behaviors (P<0.0001 and P<0.0001); thermoregulation (P<0.0001); copulation described as a reproductive behavior (P=0.003); displace and escape behaviors mostly a sign of aggressive behavior (P<0.05 and P<0.05). Ostriches are diurnal animals with a nomadic lifestyle and have higher activity during the early and late times of the day. Identification of the seasonal, sexual and time of day differences on behavior types of ostriches, provides important information for ostrich management and their welfare.
Keywords: Ostrich (Struthio camelus); climate-change; behavior; animal welfare